2019
DOI: 10.47276/lr.90.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Tuberculoid leprosy of the scalp mimicking alopecia areata-vitiligo overlap syndrome: A case report

Abstract: The scalp is known to be a zone relatively immune to Mycobacterium leprae. Regardless, there have been multiple reports of multibacillary (MB) leprosy affecting the scalp. However, less than ten paucibacillary leprosy (PB) cases with scalp involvement are known, two of which also had patches of alopecia. Herein, we report the third case of 'leprotic alopecia' in a 26-year-old female secondary to PB leprosy. Although the clinical picture mimicked alopecia areata-vitiligo overlap syndrome, histopathological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Mycobacterium leprae prefers colder areas of the human body, 1 a direct implication of which is the development of “ Immune zones ” in leprosy—the scalp, axillae, genitalia, groin, eyelids, transverse band of skin overlying lumbosacral area, and the perineum. Most studies on leprosy with scalp involvement as well as mild and moderate infiltration showed no impairment of the vital part of the follicle as the deeper areas are not affected 2–4 . In our patient, however, there was a significant destruction of the hair follicles leading to patchy cicatricial alopecia.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…Mycobacterium leprae prefers colder areas of the human body, 1 a direct implication of which is the development of “ Immune zones ” in leprosy—the scalp, axillae, genitalia, groin, eyelids, transverse band of skin overlying lumbosacral area, and the perineum. Most studies on leprosy with scalp involvement as well as mild and moderate infiltration showed no impairment of the vital part of the follicle as the deeper areas are not affected 2–4 . In our patient, however, there was a significant destruction of the hair follicles leading to patchy cicatricial alopecia.…”
Section: Discussioncontrasting
confidence: 43%
“…Most studies on leprosy with scalp involvement as well as mild and moderate infiltration showed no impairment of the vital part of the follicle as the deeper areas are not affected. [2][3][4] In our patient, however, there was a significant destruction of the hair follicles leading to patchy cicatricial alopecia.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations